2019
DOI: 10.1007/s00787-019-01340-6
|View full text |Cite|
|
Sign up to set email alerts
|

Long-term mental health in unaccompanied refugee minors: pre- and post-flight predictors

Abstract: Unaccompanied refugee minors are a particularly vulnerable group. The aim of this study is to increase our knowledge about possible pathways to wellbeing and integration for unaccompanied refugee minors as they strive to establish new lives in a host county. The present study followed a group of youth who fled to Norway without their caregivers at three time points; 6 months (n=95; M age=13.8, 80% boys), 2 years (n=78; M age = 16.5, 83% boys), and 5 years (n=47; M age 20.0, 83% boys) after arrival. Linear mixe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
96
3
8

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(116 citation statements)
references
References 48 publications
9
96
3
8
Order By: Relevance
“…The high rates of "at risk" children presented are therefore particularly concerning, as they raise questions regarding whether the PTSD prevalences have declined over time, remained stable or even increased post arrival. Prior longitudinal studies exploring the mental health of unaccompanied refugee minors have found sustained levels of PTSD symptoms over time, even while other measures of mental disorders declined [8,49]. While the present study did not collect longitudinal data, the findings herein might be consistent with these cited studies.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The high rates of "at risk" children presented are therefore particularly concerning, as they raise questions regarding whether the PTSD prevalences have declined over time, remained stable or even increased post arrival. Prior longitudinal studies exploring the mental health of unaccompanied refugee minors have found sustained levels of PTSD symptoms over time, even while other measures of mental disorders declined [8,49]. While the present study did not collect longitudinal data, the findings herein might be consistent with these cited studies.…”
Section: Discussionsupporting
confidence: 86%
“…Indeed, research focusing on refugee children and unaccompanied refugee minors has consistently reported heightened risk for mental health disorders, including posttraumatic stress disorder (PTSD), within this population and existing evidence suggests that mental health disorders tend to be highly prevalent, even several years after resettlement [3][4][5][6][7][8][9][10][11][12]. Prior research has shown that a number of factors are associated with the development of mental health problems in refugee children and adolescents, such as exposure to violence, stress in the postmigration context, family stress, separation from parents, and discrimination [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies report that 52% have posttraumatic disorders, 44% depressive syndromes, and 38% an anxiety disorder (1)(2)(3)(4). For around a third of these adolescents, these disorders go on to become chronic (5), especially those with anxious or posttraumatic symptoms (6).…”
Section: Introductionmentioning
confidence: 99%
“…On the ontogenetic level, a higher exposure to war-related traumatic events is a powerful risk factor for refugee children's mental health across settings [2,9]. Cumulative premigration trauma predicted higher levels of PTSD symptoms, depression, and anxiety in longitudinal studies with refugee minors in Norway [10] and Belgium [11]. Although the way refugee children cope with their adverse experiences is likely crucial for their mental health, there has been little research on the role of coping strategies [7].…”
Section: Introductionmentioning
confidence: 99%